Pengaruh Penggunaan Metode Pemberian Tugas Rumah Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam di SMA Muhammadiyah 18 Sunggal - Emmi Hairani Hasibuan; Widya Masitah (Al-Ulum: Jurnal Pendidikan Islam, 2022)
The purpose of writing this research is to determine the effect of using the method of giving homework on the learning outcomes of class X students in Islamic religious education subjects. This study uses a quantitative method with an associative approach (ex-post pacto). The population in this study were all class X SMA Muhammadiyah 18 Sunggal totaling 64 students. The results of the study concluded that there was no influence or low effect of the method of giving homework on student learning outcomes in Islamic Religious Education subjects at SMA Muhammadiyah 18 Sunggal. This is evident from the results of hypothesis testing using the chi squared formula obtained by x^2 of 2.0584 which is calculated to be smaller than (x^2) at the 5% significance level with a price of 16.919, which is 2.0584. So that in research conducted by researchers on the alternative hypothesis (Ha) is rejected and (Ho) is accepted, with a very low level of relationship. The results of the calculation of the coefficient of determination the effect of using the method of giving homework has a contribution of 20.32%. In influencing student learning outcomes in Islamic Religious Education students of class X SMA Muhammadiyah 18 Sunggal.